Influence of cobalt addition on microstructure and hot workability of IN713C superalloy. (15th May 2017) - Li, Yunping; Ye, Xianjuan; Li, Jiaxiang; Zhang, Yi; Koizumi, Yuichiro; Chiba, Akihiko
Abstract: In the present research, the influence of Co addition on the microstructure and hot workability of IN713C alloy was investigated in detail by scanning electron microscope (SEM), transition electron microscope (TEM) and electron backscattering diffraction (EBSD) etc. Substitution of Ni by Co leads to lower driving force for formation of γ′ phase. In addition, with the increase of Co fraction, the γ′ phase precipitates turned finer and more cuboidal shape. As a result, the hot workability of IN713C alloy was improved significantly by Co addition. This can be ascribed to the decrease in activation energy, misfit between γ/γ′ phase lattice, the stacking fault energy as well as the fraction of γ′ phase at elevated temperature after adding Co. Graphical abstract: Highlights: γ′ Phase evolves into cuboidal shape from irregular shape with Co addition. Co additions enhance the hot workability of IN713 superalloy. Co additions enhance the DRX of IN713C superalloy. Enhanced DRX is ascribed to the low SFE and low activation energy after Co addition.